Chapter 3 Mestrer jeg trenerrollen? - Ommundsen, Yngvar (Cappelen Damm Akademisk/NOASP (Nordic Open Access Scholarly Publishing), 2018)
"The purpose of this study was to examine factorial, convergent, discriminant, and criteria validity of a multi-dimensional scale measuring coaching efficacy (Feltz, Chase, Moritz, & Sullivan, 1999). The sample consisted of 281 Norwegian grassroot football coaches taking part in two data collections (across the football season) within the Norwegian arm of the international PAPA project (intervention group, n = 193) and control group, n = 88). Latent variable modeling supported a 4-factor model reflecting Motivation efficacy, Strategy efficacy, Technique efficacy and Character efficacy. An introductory ESEM analysis of the 24-item coaching efficacy scale yielded an acceptable solution after omitting two items. A parceling approach of the twenty-two items were then converted into eleven parcels to examine factorial validity and time and group invariance. The four-factor model based on parcels obtained good fit indices: (S-B χ2 = [df = 29, n = 222] = 38.622, p < .011 (ns.); RMSEA = .039; 90% (CI = .000-.068); CFI = .99; SRMR = .023). Moreover, we obtained strong support for time invariance for a merged solution of the two groups of coaches. Invariance across time for the intervention and control group separately was supported at time 1, but not at time 2. Satisfactorily convergent, discriminant, and criteria validity were also supported. The scale needs further validation before use in intervention studies."